THE EFFECT OF PROVIDING BANANA (MUSA PARADISIACA L) PEEL EXTRACT ON THE GROWTH OF CAYENNE PEPPER (capsicum frutescens l) - Habibul Akram (CV Naskah Aceh, 2024)
To determine the effect and to know the volume of extract of giving kepok banana peel extract (Musa paradisiaca L) on the growth of cayenne pepper (Capsicum frutescens L). The population in this study included all types of cayenne pepper. This research used a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The research results for stem height (cm) were calculated based on analysis of variance, the average value starting at the age of 10 days, the calculated F value (1.28) < F table (3.48), at the age of 15 days the calculated F value (8.45) > F table (3.48), at the age of 20 days the calculated F value (11.82) > F table (3.48) and at the age of 25 days the calculated F value (10.72) > F table (3.48) Thus, it can be concluded that the administration of Kepok banana peel extract had a significant effect on the height growth of cayenne pepper plants at the ages of 15, 20 and 25, whereas at the age of 10 days there was no effect.